Cytomorphological evaluation of squamous cell abnormalities observed on cervical smears in government medical college, Jabalpur, India: a five year study - Nandwani, Radhika Rajesh; Totade, Sanjay; Krishnan, Murali Gopala (International Journal of Research in Medical Sciences, 2016)
Background: Cervical cancer is the fourth most common cancer affecting women worldwide, the most common cancer in women in several less developed countries, and now the second most common cancer in India. Cervical cytology by papanicolaou (PAP) smear test is an effective tool for detecting abnormal cytology in early stages, thus allowing early detection and treatment. The PAP smear is extremely important for detecting premalignant and malignant conditions of cervix. The study was conducted to determine; (1) Cytomorphologic incidence of various lesions of uterine cervix; (2) Categorization of detected lesions according to Bethesda system; (3) Determination of epithelial abnormalities by cervical cytology. Methods: The settings and design of this study is a hospital based prospective study from a tertiary care centre in Central India. A total of 5813 conventional pap smear tests collected from January 2010 and December 2014 were analyzed. All patients attending outpatient department of obstetrics and gynecology for complaints of abnormal cervical discharge, dyspareunia, inter-menstrual bleeding, post-coital bleeding and lower abdominal pain were included. Various cervical pap screening camps were also done during this period. Smears were fixed and stained with hematoxylin & eosin (H&E) and papanicolaou stain were done. Results: The overall frequency of normal, inadequate, inflammatory, and abnormal smears was 11.86%, 5.73%, 74.98% and 13.2% respectively. Atypical squamous cell carcinoma of undermined significance (ASCUS) was seen in 3.61%, squamous intraepithelial lesion (SIL) was seen in 5.36%, low grade squamous intraepithelial lesion (LSIL) was seen in 2.59% while high grade squamous intraepithelial lesion (HSIL) was seen in 2.77%. Invasive carcinoma was seen in 3.69%. The premalignant epithelial abnormalities like ASCUS, LSIL and HSIL were found to be highest in the age group of 31-50 years in our study, which correlated well with other similar studies. Conclusions: Hence we should advocate regular cervical cytology (PAP) smear study, which can help to treat cervix lesions early before the progress into cervical cancer. Early detection is the only key to saving a woman’s life as the later the abnormalities are discovered; mortality, morbidity and treatment cost all increase.